Cholera Vibrio Virulence Strategy and Ways of its Realization (Scientific Review) - E. V. Monakhova (Проблемы особо опасных инфекций, 2013)
The basic ways of Vibrio cholerae virulence strategy realization through acquisition and expression of genes of various toxic substances are discussed. Considered are molecular mechanisms responsible for interaction between host organism and cholera vibrios, as well as for genetic information exchange, for accumulation and loss of determinants of factors, which are non-identical structurally but functionally similar. Based on the analysis of literature data and personal observations put forward is a conception of pathogenicity factor intersubstitutability allowing for restoration and maintenance of pathogenetic potential of severe diarrheal disease agents among the strains deprived of cholera toxin genes.